2012
DOI: 10.1002/jmri.23709
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of forearm nerves in humans

Abstract: Purpose To implement diffusion tensor imaging (DTI) protocol for visualization of peripheral nerves in human forearm. Materials and Methods This HIPAA-compliant study was approved by our institutional review board and written informed consent was obtained from 10 healthy participants. T1-and T2-weighted turbo spin echo with fat saturation, short tau inversion recovery (STIR), and DTI sequences with 21 diffusion encoding directions were implemented to acquire images of the forearm nerves with an 8 channel kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 33 publications
3
56
0
Order By: Relevance
“…The FA maps at higher spatial resolution, acquired with the optimized DTI scan parameters allowed visualization of the superficial radial, median, and ulnar nerves consistently on all the scans, whereas only ulnar and median nerves were clearly visualized at lower spatial resolution (). We believe that our studies are the first to systematically evaluate the effect of various acquisition parameters on the visualization and quantification of the diffusion anisotropy in peripheral nerves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FA maps at higher spatial resolution, acquired with the optimized DTI scan parameters allowed visualization of the superficial radial, median, and ulnar nerves consistently on all the scans, whereas only ulnar and median nerves were clearly visualized at lower spatial resolution (). We believe that our studies are the first to systematically evaluate the effect of various acquisition parameters on the visualization and quantification of the diffusion anisotropy in peripheral nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, DTI has attracted considerable attention for the evaluation of peripheral nerves in patients with nerve diseases and injuries, and monitoring nerve degeneration and regeneration after traumatic nerve injuries (). Quantitative DTI measures such as FA, MD, λ // , and λ ⊥ on healthy controls were obtained for comparison with the diseased/injured nerves to assess nerve integrity, repair, and other diseases (). Preclinical studies suggested the utility of specific DTI indices in assessing peripheral nerve injury and repair ().…”
mentioning
confidence: 99%
“…Recent studies on peripheral nerve DTI have demonstrated its general feasibility (8)(9)(10)(11)(12) in the accurate visualization of nerves by means of their fractional anisotropy (FA). FA indicates the directional preference of free water proton diffusion, which physiologically has high values in intact peripheral nerves (reviewed in references 9 and 13).…”
Section: Participant Datamentioning
confidence: 99%
“…Skorpil14 applied a new MRI technique, diffusion direction–dependent imaging (DDI), after processing to isolate human sciatic nerve images from surrounding tissue images, to clearly display nerve morphology. In 2012, Zhou et al 15. used the diffusion tensor imaging technique to examine median and ulnar nerves in the human forearm, which enabled to display a nerve in the human forearm with a diameter of about 3 mm.…”
Section: Discussionmentioning
confidence: 99%